ANTIBACTERIAL ASSESSMENT OF ALOE VERA (Aloe vera chinensis Linn) CORTEX EXTRACT AND ITS APPLICATION AS INHIBITOR FOR KING PRAWNS (Macrobrachium rosenbergii Linn) SPOILAGE DURING STORAGE AT 5oC - Yasmin Nabila, Muhammad Isa Dwijatmoko & Danar Praseptiangga, Dimas Rahadian Aji Muhammad, Intan Nis (Proceeding of International Congress, 2014)
Fat and sugar blooming on chocolate affects on consumer acceptance, because the existing perceptionthat blooming decrease the safety of the product. Enriching dark chocolate bar with essential oil fromcinnamon (Cinnamomum burmanii) have been conducted. This research aims to investigate the effect ofcinnamon on the blooming occurence during storage. As soon as the chocolate bloomed, FFA and TPCanalysis were performed as safety indicator. The results shows that enriching essential oil from cinnamonslackens bloom appearance on dark chocolate. The bloomed product is safe to be consumed, since FFAand TPC number are under the maximum limit of the requirements of food safety.Keywords: dark chocolate, food safety, bloom, cinnamon